KEDISIPLINAN SISWA MENGIKUTI PEMBELAJARAN PAI PASCA BELAJAR DARING DI SMKN 1 KECAMATAN LUAK KABUPATEN LIMAPULUH KOTA - Latifah Rahmadian; Charles Charles; Zulfani Sesmiarni; Supratman Zakir (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by student discipline when following the learning process. Many students are not disciplined when taking lessons, there are still many who arrive late even though class has started, there are still students who are saltum (wrong costumes) when taking lessons, and there are still some students who do not apply a commendable attitude when in the school environment. Therefore, the authors need to examine more deeply: How is the discipline of students in participating in PAI learning at SMKN 1 Luak District, Limapuluh Kota Regency. The type of research that the author uses is field research, this research uses descriptive with a qualitative approach, namely research conducted by describing the state of the object based on the facts as they are. The informants in this study were students as key informants and PAI teachers as supporting informants at SMKN 1 Luak District, Limapuluh Kota Regency. In collecting data the author uses data collection techniques, namely observation, interviews, and documentation. While the data analysis techniques that the author uses are data reduction, data presentation, and drawing conclusions or verification. Testing the validity of the data by using data triangulation techniques, namely comparing the results of observation data and interview results. Based on the results of the research that the author did at SMKN 1 Luak District, Limapuluh Kota Regency, it can be concluded that there are some students who still do not obey school rules or regulations, discipline when entering school, discipline in carrying out tasks, and discipline in following lessons at school. Keyword: Student Discipline